Efektifitas Layanan Bimbingan dan Konseling Komprehensif di Sekolah Menengah Atas - Setyawan, Akhmad (Universitas Veteran Bangun Nusantara, 2023)
Abstract The aim of this research is to find out the effectiveness of comprehensive guidance and counseling services at SMA Muhammadiyah Imam Syuhodo. The research method used is a quantitative research approach. The type of research used is experimental research, namely research intended to see the effectiveness of applying a variable. The analysis used is simple regression analysis. Based on the results of research at Muhammadiyah Imam Syuhodo High School, it can be categorized as follows: 85 students (85%) were helped by comprehensive guidance and counseling services and 15 students (15%) were not helped by comprehensive guidance and counseling services.